Short and Extra Short Dental Implants in Osseous Microvascular Free Flaps: A Retrospective Case Series - Hocková, Barbora; Slávik, Rastislav; Azar, Basel; Stebel, Jakub; Poruban, Dušan; Bonfante, Estevam A; Ewers, Rolf; Cheng, Yu-Chi; Stebel, Adam (Journal of personalized medicine, 2024)
There is limited information regarding implant and prosthetic survival after osseous microvascular free flap (OMFF). This case series aims to describe the placement of short and extra short implants in osseous microvascular free flaps to support prostheses, and present an up to 40-month retrospective follow-up. Short and extra short dental implants were placed in six fibula free flaps (FFF) and in two microvascular deep circumflex iliac artery (DCIA) flaps. In total, 27 short and extra short dental implants have been placed into two different types of free flaps. Kaplan-Meyer (K-M) survival analyses were performed to evaluate the survival and success outcomes of implants and prostheses. Out of the eight patients reconstructed with free flap, five were rehabilitated with prostheses, one patient has a temporary prosthesis, and two patients are in the process of prosthetic rehabilitation. Twenty-seven implants were followed up for up to 40 months, and K-M analyses showed 100% implant survival probability (95% confidence interval: 100%), while the implant success probability was 91.0% (95% confidence interval: 68.6-97.7%). Short and extra short dental implants placed in OMFF presented high survival and success rates in a retrospective case series after up to 40 months.
Keywords: prosthetic rehabilitation; microvascular free flap; short dental implants; osseous microvascular free tissue transfer